Analysis of Structural and Material Aspects of Selected Elements of a Hydropneumatic Suspension System in a Passenger Car - Konieczny Ł.; Burdzik R.; Węgrzyn T. (Archives of Metallurgy and Materials, 2016)
The article addresses results of analyses of design solutions and materials commonly used in gas springs for hydropneumatic suspension systems. The authors have discussed main advantages resulting from application of such a design solution in passenger car suspension systems. Fundamental correlations defining the parameters characterising a gas spring with constant gas mass have been referred to. Also materials used in the manufacture of selected gas spring elements have been described